MODEL INSTRUMEN KEBIJAKAN FISKAL ISLAM DALAM PENANGANAN COVID-19 - Bariyyatin Nafi’ah; Nur Rachmat Arifin; Farisul Haq (Ulumuna: Jurnal Studi Keilsman, 2021)
This research was conducted with the aim of describing some of the solutions for Islamic economic and financial policies that can be offered in the face of the Covid-19 pandemic in Indonesia. This study uses a descriptive qualitative approach with content analysis techniques (content analysis) and library research (library research). The results of the study indicate that among the solutions that can be offered within the framework of the concept and economic system in Islamic Fiscal policy: (1) by distributing direct cash assistance from zakat, infaq and alms; (2) by strengthening waqf in the form of cash waqf, productive waqf, sukuk linked waqf and waqf for infrastructure; (3) through leading business capital assistance for the business sector or Micro, Small and Medium Enterprises (MSMEs); (4) through the qardhul hasan scheme.